Sustainable leadership styles adopted by small businesses in the UAE during and post COVID-19 - Ansarullah Tantry; Sayed Abdul Majid Gilani; Saher Al Sabbah; Charli Sitinjak; Nida Khan; Tausif Mulla; Soumaya Askri; Rayees Mohammad Bhat (Discover Sustainability)
Abstract COVID-19 emerged in late 2019 as a global crisis which led to major government restrictions on global populations. This had a detrimental impact on the survival and growth of smaller businesses. The resilience of smaller to medium enterprises (SMEs) was crucial to global economies as SMEs represent over 90% of businesses worldwide. However, due to the recent conclusion of COVID-19, there appears to be limited/no studies investigating the change in strategies adopted by businesses during the pandemic. The United Arab Emirates (UAE) established itself as the hub of business activity between Western and Eastern countries, however, this was halted by COVID-19. This study aimed to address this gap by examining the leadership philosophies adopted by SMEs in the UAE during the pandemic. Using a qualitative approach, semi-structured interviews were conducted with 70 SMEs between September and December 2023, and the data were analysed through thematic analysis. Out of the 70 interviewed SMEs, 42 SMEs changed their leadership style during the pandemic whereas 28 SMEs did not change their style. Sustainable leadership style was the most adopted style by SMEs in the UAE during the pandemic followed by transactional. After the pandemic era, the sustainable style was adopted by 46 SMEs, the transactional style is adopted by 24 SMEs and the transformational style is adopted by 10 SMEs. The findings suggested that most SMEs embraced sustainable leadership styles, characterized by agile decision-making, long-term resilience, and adaptive strategies shaped by pandemic-induced challenges. The findings contribute to the existing literature by providing insights into how small businesses in the UAE adapted their leadership approaches to maintain resilience and ensure business continuity during crises. Moreover, the study highlights the relevance of sustainable leadership in enhancing organizational adaptability and long-term survival in challenging environments, offering practical implications for business leaders and policymakers in developing crisis-resilient leadership frameworks.